Przełożyć czy przetłumaczyć tekst literacki? - Tokarz, Bożena (Przestrzenie Teorii, 2023)
Tone Pretnar, in the translation of Jan Nepomucen Kamiński’s sonnets, created the illusion of the original by using his own poetic talent and a foreign word. Just as Kamiński used the word of Mickiewicz, so he used the word of Prešeren. However, he changed the communication purpose of the original text. Apart from the pastiche aspect, he gave the original a high poetic value, while revealing the aporia of the original’s autonomy.